2010
DOI: 10.1200/jco.2009.23.7172
|View full text |Cite
|
Sign up to set email alerts
|

Major Tumor Shrinking and Persistent Molecular Remissions After Consolidation With Bortezomib, Thalidomide, and Dexamethasone in Patients With Autografted Myeloma

Abstract: PURPOSE We investigated the effect on minimal residual disease, by qualitative and real-time quantitative polymerase chain reaction (RQ-PCR), of a consolidation regimen that included bortezomib, thalidomide, and dexamethasone (VTD) in patients with multiple myeloma (MM) responding to autologous stem-cell transplantation (auto-SCT). PATIENTS AND METHODS Patients achieving at least very good partial response who had an available molecular marker based on the immunoglobulin heavy-chain rearrangement received four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(195 citation statements)
references
References 43 publications
7
186
0
2
Order By: Relevance
“…38 As an alternative, ASO realtime quantitative PCR provides an accurate quantification of residual disease, thus overcoming the problem. Several reports using this technique have been published, showing effective outcome discrimination in the transplant setting 29,[39][40][41][42][43] (Table 5). …”
Section: Novel Methods To Measure Mrdmentioning
confidence: 99%
“…38 As an alternative, ASO realtime quantitative PCR provides an accurate quantification of residual disease, thus overcoming the problem. Several reports using this technique have been published, showing effective outcome discrimination in the transplant setting 29,[39][40][41][42][43] (Table 5). …”
Section: Novel Methods To Measure Mrdmentioning
confidence: 99%
“…Similarly, Ladetto et al 23 treated patients who had achieved at least a very good partial response following ASCT with four cycles of VTD consolidation and observed not only an increase in CR rates, but also in molecular remissions, which were found to be persistent as no patient with molecular remissions had relapsed at a median follow-up of 42 months. A retrospective study reported by Leleu et al 24 also showed the benefit of VTd (bortezomib-thalidomide-low dose dexamethasone) consolidation (with dexamethasone administered at 40 mg weekly) after a single ASCT following VTd induction.…”
Section: Consolidation Therapymentioning
confidence: 99%
“…As already mentioned, the definition of CR is far from optimal, and sensitive techniques will contribute to the evaluation of minimal residual disease both at bone marrow (BM) level (by using molecular techniques, quantitative PCR, and immunophenotyping techniques such as flow cytometry) 13,18,19 and outside the BM (using imaging techniques such as MRI and PET-CT). [20][21][22] If myeloma continues to be evaluated by the M-component and morphology it will remain the Cinderella of hematologic malignancies in terms of the resources invested in monitoring treatment efficacy.…”
Section: -14mentioning
confidence: 99%
“…Thus, the benefit of treatment intensification in low-risk patients was recently demonstrated in a cohort who, although they were already in more than VGPR after ASCT, received intensification with VTD, and none of those who achieved a molecular remission has so far relapsed. 13 Accordingly, the risk of undertreating low-risk patients by concluding that they are already in conventional CR could be a serious error if cure is the goal. Clinical investigation based on large phase III randomized trials that integrate comprehensive genetic studies upfront and sensitive tools for monitoring treatment efficacy will be the best way to find appropriate answers to these questions.…”
Section: -14mentioning
confidence: 99%